2010
DOI: 10.4141/cjas09047
|View full text |Cite
|
Sign up to set email alerts
|

Feeding amount affects the sorting behavior of lactating dairy cows

Abstract: Miller-Cushon, E. K. and DeVries, T. J. 2010. Feeding amount affects the sorting behavior of lactating dairy cows. Can. J. Anim. Sci. 90: 1Á7. The objective of this study was to determine whether feed sorting behavior in dairy cattle is influenced by the amount of feed provided. Six lactating Holstein cows, individually fed a total mixed ration once daily, were exposed to two treatments in a crossover design with 7-d periods. The treatments were: (1) lower feed amount (LFA; target 10% orts), and (2) higher fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
11
2
Order By: Relevance
“…Heifers were provided feed in excess (>20% refusals), providing them with much more long particles to select for than if provided a ration consumed with limited to no refusals. Work with dairy cattle has shown that sorting of mixed rations increases linearly with the amount of feed refusals (Leonardi and Armentano, 2007;Miller-Cushon and DeVries, 2010). Therefore, the sorting observed in the current study was likely exacerbated by the high level of feeding.…”
Section: Discussionmentioning
confidence: 65%
“…Heifers were provided feed in excess (>20% refusals), providing them with much more long particles to select for than if provided a ration consumed with limited to no refusals. Work with dairy cattle has shown that sorting of mixed rations increases linearly with the amount of feed refusals (Leonardi and Armentano, 2007;Miller-Cushon and DeVries, 2010). Therefore, the sorting observed in the current study was likely exacerbated by the high level of feeding.…”
Section: Discussionmentioning
confidence: 65%
“…Feed sorting behavior is typically addressed through feed management strategies applied at the herd level, such as adjusting ration DM content (Leonardi et al, 2005;Miller-Cushon and DeVries, 2009), feeding level (Miller-Cushon and DeVries, 2010), and feeding frequency (DeVries et al, 2005).…”
Section: Short Communicationmentioning
confidence: 99%
“…Individual feed intake was determined daily by weighing the amount of feed offered and the amount refused. Actual feeding level (% orts) was compared between treatments to ensure that treatment was not confounded with feeding level, which has been found to affect degree of feed sorting (Leonardi and Armentano, 2007;Miller-Cushon and DeVries, 2010).…”
Section: Experimental Design and Dietsmentioning
confidence: 99%